2019
DOI: 10.3390/jcm8111867
|View full text |Cite
|
Sign up to set email alerts
|

Secretome and Extracellular Vesicles as New Biological Therapies for Knee Osteoarthritis: A Systematic Review

Abstract: Secretome and extracellular vesicles (EVs) are considered a promising option to exploit mesenchymal stem cells’ (MSCs) properties to address knee osteoarthritis (OA). The aim of this systematic review was to analyze both the in vitro and in vivo literature, in order to understand the potential of secretome and EVs as a minimally invasive injective biological approach. A systematic review of the literature was performed on PubMed, Embase, and Web of Science databases up to 31 August 2019. Twenty studies were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 45 publications
(200 reference statements)
2
52
0
Order By: Relevance
“…Although it is quite well-accepted that MSCs act through paracrine mechanisms on resident cells, nevertheless, a thorough characterization of soluble factors and EV content is lacking and would be essential to define MSCs and MSC-enriched products. In this perspective, in the last years, researchers have tried to couple the array of secreted molecules with the observed protective effects in clinical experiences [58,59]. Despite valuable hints, very often, the input datasets had two major flaws.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is quite well-accepted that MSCs act through paracrine mechanisms on resident cells, nevertheless, a thorough characterization of soluble factors and EV content is lacking and would be essential to define MSCs and MSC-enriched products. In this perspective, in the last years, researchers have tried to couple the array of secreted molecules with the observed protective effects in clinical experiences [58,59]. Despite valuable hints, very often, the input datasets had two major flaws.…”
Section: Discussionmentioning
confidence: 99%
“…Current research on regenerative approaches for cartilage recovery focuses on EVs derived from mesenchymal stem/stromal cells (MSCs) obtained from adipose tissue (A-MSC), bone marrow (BM-MSCs), or embryonic stem cells (ESC-MSCs) (D'Arrigo et al, 2019;Li et al, 2019). EVs from A-MSCs were shown to increase cartilage matrix synthesis indicated by type II collagen (COL2A1) expression and reduced expression of catabolic enzymes such as matrix metalloproteinase 13 (MMP13) and a disintegrin and metalloproteinase with thrombospondin motifs 5 (ADAMTS5) in OA chondrocytes (Wu et al, 2019), while reducing inflammation via promoting transition to the M2 phenotype of macrophages (Lo Sicco et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Only few preclinical studies focused on the intraarticular injective use of BMAC for OA, while the majority of these studies focused on culture-expanded BMSCs or on surgical applications of BMAC, including the treatment of focal cartilage defects (surgical augmentation or scaffoldbased applications) [14,70,71]. The few preclinical studies in the literature suggested that BMAC can affect OA progression in the animal models, but they also underlined its limited potential, and the possibility to further exploit it through different production protocols as well as the combination of injective carriers to positively affect cell migration and favor longer-lasting homeostatic and disease-modifying effects [51,72].…”
mentioning
confidence: 99%